Managing Motherhood A New Wellness Perspective - Currie, Janet L. (SpringerBriefs in Well-Being and Quality of Life Research,, 2018)
This book asserts that women attain higher levels of health in the mothering role when they achieve increased control over their own health, lifestyle and environment. Reflecting the philosophy of health promotion, it explores the meaning of the positive coping experience for new mothers, identifying the essential features of resilience in a new coping model based on ground-breaking analytical techniques. Further, the book discusses preventative strategies for building resilience and quality of life during the period of new motherhood, opening new horizons and dialogues related to what "coping" can actually mean when underpinned by a well-being paradigm. .